(3CMcGe JTZjd GdCLGfH (B: s (3OQGSI ebGQfI (B/ s - (3jGSQ MeOi jS EHQGgjes; (3CMeO MSf GdHQYj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2017)
(3CMcGe JTZjd GdCLGfH ai GdbGfhf GdebGQf(B: (3ef Cge GdehVhYGJ Ydi GdeSJhjjf GdOhdi h GdOGNdi(B: (3h JHOh gPg GdCgejI(B: (3ai JWhQ hVY GdCLGfH NdGd GdYUhQ GdhSWi HbjGe GdKhQI GdaQfSjI YGe (B1789: (3GdJi GfJTQJ eYgG GdeHGOiA GdJi JbQQ GdCNhI Hjf GdTYhH GdeNJdaI(B: (3h bO GSJbQJ gPg GdMbhb ai GdVejQ GdEfSGfi(B: (3HGYJHGQgG JeKd GdHfjGf GdPi jLH Cf jbhe Ydjg fXGe GdMce(B: (3dCi OhdI(B. (3h XgQJ LghO cd ef efXeI GdYed GdOhdjI(B: (3h efXeI GdYed GdYQHjI(B: (3HGYJHGQgeG ef GdhcGdGJ GdeJNUUI ai eLGd YdGbGJ GdYed h bVGjG GdYeGd dJhJL gPG GdeLghO HEUOGQ GdeYGjjQ GddGReI ai h UQI EJaGbjGJ(B: (3h jUOQ eDJeQ GdYed GdOhdi GdJGHY defXeI GdYed GdOhdjI ai cd OhQI ef OhQGJ GfYbGOg YOOkG ef GdGJaGbjGJ h GdJhUjGJ GdJi JJfGhd eNJda bVGjG GdYed(B. (3h CjVG efXeI GdYed GdOhdjI GdJi Jbhe HEUOGQ GJaGbjGJ LeGYjI JdJRe HgG GdOhd GdCYVGA ai GdefXeI h HOi ef NdGd gPg GdOQGSI Cfg dG jhLO GdjGJ eMOOI ai efXeI GdYed GdOhdjI JdRe GdOhd HGdGdJRGe HGdeYGjjQ GdOhdjI GdJi JbQQgG ai GdGJaGbjGJ h GdJhUjGJ GdJi jUOQgG eDJeQ GdYed GdOhdi h cPdc efXeI GdYed GdYQHjIs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2017.s
(3HHdjhLQGajG(B: (3UaMGJ(B282-318.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3JTZjd GdCLGfHs; (3MQjI GdYeds; (3Mb GdYeds; (3GdGJaGbjI GdOhdjI dMeGjI Mbhb LejY GdYeGd s; (3Mbhb GdEfSGf hGdYGed GdegGLQ s; (3OhQ GdefXeGJ GdOhdjI aj MeGjI GdYeGd GdCLGfH s; (3efXeI GdYed GdOhdjI s; (3GdYGed GdegGLQ s; (3GJaGbjI GdhMOI GdGbJUGOjI YGe (B1957 s; (3GdMO GdCOfi deYGedI GdCLGfH s; (3TQW GdeYGedI HGdeKd s; (3TQW GdMUhd Ydi JQNjU HGdYed s; (3Gdegf GdMQI s; (3Jedc hEOGQI GdCLfHj ddTQcGJ GdeSGgeI s; (3GdeSJCefs; (3eYGgOI GdEbGeI s; (3JQNjU s; (3JTZjd GdCLGfHs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2017